Competitiveness of Peru and South America in rice (Oryza sativa) and potato (Solanum tuberosum) production - Anderson Seminario, María de las Mercedes (2021)
Peru and South America have achieved benefits with the expansion of trade flows, but there would be competitive weakness in two of their emblematic products: rice and potato. It was analyzed how competitive Peru and South America are in the production of rice and potatoes, using the revealed comparative advantage method, finding that the Relative Trade Balance (BCR) is less than 0 for both products in Peru being a net importer of both products (BCR potato -0.859 and rice -0.891) and less than 1 for South America, the BCR of potato -0.375 classifies it as a net importer and that of rice (0.280) shows a slight export trend. It is concluded that neither South America nor Peru is competitive in these crops, although some countries in South America export rice (Uruguay) and potato (Chile and Argentina). The results of the revealed competitiveness indicators determine those Peruvian potatoes and rice are not competitive products at the international trade level. Exports are not significant, which indicates that production is basically directed to the domestic market. While competitiveness as a region in relation to the world is also considered low, countries must import these products to satisfy their demand, it is only Uruguay that presents a better level of openness to international trade.